High-resolution comparative single-cell transcriptomics of doublesex -expressing neurons reveals evolutionary conservation and diversity of sexual circuits in Drosophila - Walsh, Justin; Junker, Ian P; Chen, Yu-Chieh David; Chen, Yen-Chung; Gifford, Helena; Ding, Yun (bioRxiv, 2025)
Understanding how the cellular and molecular composition of neural circuits change during evolution is essential for deciphering how behavior evolves. Male sexual behaviors in species are remarkably diverse, and the underlying sexual circuits are specified by sex determination genes. Here, we employed single-cell transcriptomics to systematically characterize and compare neuron cell types that express the sex determination gene in adult males across species with divergent sexual behaviors. High-resolution profiling to delineate cellular diversity revealed a largely conserved set of cell types across four species, with minimal evolutionary gain or loss and potentially more prevalent changes in cell type abundance. In-depth comparisons between and showed that transcriptomic conservation and differentially expressed genes between species are highly cell-type-specific, suggesting that cell types evolve as highly independent units. We identified widespread species differences in gene expression, particularly in the neuromodulatory signaling pathway, while preserving a conserved circuit layout in sexual identity and neurotransmitter properties. We further generated a female dataset in to define sex differences in cell types and examine species divergence in relation to sex differences. Finally, we reported marker gene combinations that uniquely define each cell type, providing a foundational resource that enables the design of cell -type-specific genetic reagents. Overall, our study provides fundamental insights into the cellular diversity of sexual circuits and how evolution shapes cell types and gene expression in behavioral adaptations.